Office girl ebook A novel. - Meno, Joe (2012)
This quirky tale of two young artists in love in 1990s Chicago is “a gorgeous little indie romance . . . A sweetheart of a novel” ( Kirkus Reviews ).   In the last year of the twentieth century, Odile is a lovely twenty-three-year-old art-school dropout, a minor vandal, and a hopeless dreamer. Jack is a twenty-five-year-old shirker who’s most happy capturing the endless noises of the city on his out-of-date tape recorder. Together they decide to start their own art movement, in defiance of a contemporary culture made dull by both the tedious and the obvious. Set just before the end of one world and the beginning of another, this is the story of two people trying to capture a moment in the face of an uncertain future.   Named a Best Book of the Year by Daily Candy and chosen as a favorite fiction work of the year in The Believer ’s readers’ poll, Office Girl “reads as a parody of art-school types . . . and as a tribute to their devil-may-care spirit” ( The New York Times Book Review ).   “Mr. Meno excels at capturing the way that budding love can make two people feel brave and freshly alive to their surroundings . . . The story of the relationship has a sweet simplicity.” — The Wall Street Journal   “Meno’s tender, hip, funny, and imaginative portrayal of two Chicago misfits . . . dramatizes that anguished and awkward passage between legal age and actual adulthood.” — Booklist   Features black-and-white illustrations by artist Cody Hudson and photographs by Todd Baxter.